The Banking Crises Reflected in the Financial Order of the Real World - Maier, Helmut (Odzwierciedlenie kryzysu bankowego w świecie finansów, 2009)
The article reflects the present banking and financial crisis on the basis of latest research results about the existence of superior economic and financial order acting within the real world (equal natural world). Within this order (equal natural order) observably all creatures use different types of energy like different currencies of money as means of payment in order to finance, produce, and use their own life (equal own living biomass able to provide services); exemplary proof is given. Decisive message reflected in and substantiated by this order is: issuing human money being only a copy of energy with nearly full lack of real value needs coverage in the natural equivalent of money which means coverage in energy of human beings and/or assets including the energy of different creatures, and not coverage in gold or different mass measures. The author shows that China is also involved in crisis. He concludes that public measures of governments to provide more (human) money in present do not solve this crisis, rather they cause a delay and smoothing of its negative impacts by broadening the basis of responsibility within human societies of present and future. A final solution if wanted must consider the rules and constraints of this natural economic order the knowledge of which is to be enlarged urgently.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 84, s. 141-153
Keywords: banking crisis; financial policy; natural economics